Efektivitas Pijat Bayi terhadap Peningkatan Kualitas Tidur Bayi - Shinta Lutfiani; Kartika Sari; Sita Salsha Bellatika; Yulinda Yasa Putri; Vanisa; Nur Baiti (Universitas Ngudi Waluyo, 2022)
Infancy or toddlerhood is a golden period for children's growth and development that needs special attention. One of the factors that influence growth and development is sleep and rest. Deep sleep is very important for the baby's growth, because during sleep the baby's brain growth reaches its peak (Vina, 2010 in Minarti 2012). Therefore, babies who sleep longer, the baby's growth and development will be achieved optimally and it will allow the baby's body to repair and renew all cells in the body (Walker et al., 2017). The quality of baby sleep can be obtained by paying attention to the way of sleep, the environment, as well as comfort and sleep patterns. Such as paying attention to room temperature, comfortable clothes, room lighting and giving touches such as massage (orreca, et al. 2017). Many experts have proven that infant massage performed by parents (especially mothers) can provide many benefits such as weight and length, better sleep, relief and reduction of abdominal pain, better physiological and behavioral responses (Dalili et al., 2016). The purpose of this study was to determine the effectiveness of infant massage on respiratory distress and improved infant sleep quality. The method used is analysis with literature review studies. The source for conducting this literature review uses Google Scholar and ProQuest. At the journal search stage using the keyword